SENTENCE STRUCTURE ON THE ENGLISH LITERATURE STUDENTS’ THESIS ABSTRACT - Silvia Utami (English Department, University of Riau Kepulauan, Batam,Indonesia, 2021)
The thesis abstract is the opening section of the thesis, and it serves to convey the research's substance in a concise manner. Even though it is less than 200 words long, it contains important information, and well-constructed sentences are required while writing thesis abstracts. The objective of this study was to categorize the sentence structure produced by English literature students' in the thesis abstracts into two categories: grammatical and ungrammatical sentences, and to present the ungrammatical sentence structure in a tree diagram by using Phrase Structure Rules (PSRs) by Carnie (2013). This study was descriptive qualitative research that is concerned with structures and patterns especially the sentence patterns. The findings showed that most sentences were constructed in ungrammatical structure with 61% of total sentences and 39% of grammatical structure. Ungrammatical sentences were mostly caused by issues with noun agreement, to-infinitive, prepositions, and articles. This study concluded that students need to improve their linguistic competence by learning linguistic concepts about the sentence structure, and its effect on the meaning.